Carbon electrodes enable flat surface PDMS and PA6 triboelectric nanogenerators to achieve significantly enhanced triboelectric performance. (January 2019) - Shi, Lin; Dong, Shurong; Ding, Peng; Chen, Jinkai; Liu, Shuting; Huang, Shuyi; Xu, Hongsheng; Farooq, Umar; Zhang, Shaomin; Li, Shijian; Luo, Jikui
Abstract: As a promising nanoenergy technology to harvest mechanical energy from environment, triboelectric nanogenerator (TENG) has attracted much attention and various strategies focused on optimization of triboelectric materials have been proposed to further improve its output power density. This work focuses on the electrode material for improvement of TENGs. A commercial double-sided conductive carbon tape composed of carbon powder is proposed as the electrodes for TENGs, based on which a superior performance TENG comprised of spin-coated flat polydimethylsiloxane (PDMS) and polyamide-6 (PA6) films is fabricated. Owing to the strong additional interaction between carbon electrode and tribo-layer, a 20 × 20 mm 2 carbon-PDMS/PA6 TENG demonstrates a peak output voltage of ~ 1760 V, a short-circuit current density of ~ 240 mA m −2, and a maximum power density of ~ 120 W m −2, much higher than those of aluminum electrode-based Al-PDMS/PA6 TENGs. Detailed investigations reveal that the dramatically enhanced performance originates from the additional interaction in the pores between coarse carbon electrode and PDMS film, and from the enhanced electric negative polarity of PDMS films with the peeling and transferring treatment. This study provides a promising simple and low-cost strategy of selecting and preparing electrode materials with special micro/nanostructures to interact with triboelectric layers to generate additional triboelectric charges for high performance TENGs. Graphical abstract: Conductive carbon tapes with coarse surfaces are utilized as the electrodes for flat surface PDMS/PA6 triboelectric nanogenerators (TENGs), that demonstrate an outstanding electric output with a peak output voltage of ~ 1760 V, a short-circuit current density of ~ 240 mA m −2 and a maximum instantaneous power density of ~ 120 W m −2, the highest output for a TENG without using specific surface micro-structures and multi-layer structures so far. This study proposes a promising simple and low-cost strategy of selecting and preparing electrode materials with special micro/nanostructures to interact with triboelectric layers to generate additional triboelectric charges for high performance TENGs. fx1 Highlights: Conductive carbon tapes with coarse surface and high electric affinity have been utilized as the electrodes to enhance TENG performance. Carbon-PDMS/PA6 TENG demonstrates ultrahigh triboelectric performance and stability. Interaction between PDMS film and coarse carbon electrode dramatically enhances the charge density of the Carbon-PDMS/PA6 TENG.